Characterization of blaNDM-5-and blaCTX-M-199-Producing ST167 Escherichia coli Isolated from Shared Bikes - Qiyan Chen; Zhiyu Zou; Chang Cai; Hui Li; Yang Wang; Lei Lei; Bing Shao (MDPI AG, 2022)
Shared bikes as a public transport provide convenience for short-distance travel. Whilst they also act as a potential vector for antimicrobial resistant (AR) bacteria and antimicrobial resistance genes (ARGs). However, the understanding of the whole genome sequence of AR strains and ARGs-carrying plasmids collected from shared bikes is still lacking. Here, we used the HiSeq platform to sequence and analyze 24 Escherichia coli isolated from shared bikes around Metro Stations in Beijing. The isolates from shared bikes showed 14 STs and various genotypes. Two blaNDM-5 and blaCTX-M-199-producing ST167 E. coli have 16 resistance genes, four plasmid types and show >95% of similarities in core genomes compared with the ST167 E. coli strains from different origins. The blaNDM-5- or blaCTX-M-199-carrying plasmids sequencing by Nanopore were compared to plasmids with blaNDM-5- or blaCTX-M-199 originated from humans and animals. These two ST167 E. coli show high similarities in core genomes and the plasmid profiles with strains from hospital inpatients and farm animals. Our study indicated that ST167 E. coli is retained in diverse environments and carried with various plasmids. The analysis of strains such as ST167 can provide useful information for preventing or controlling the spread of AR bacteria between animals, humans and environments.